중국인, 베트남인 한국어 학습자의 언어적 불손 표현에 대한 인식 연구 - 황선영 (이중언어학, 2020)
This study aims to see the differences among Chinese Korean Learners(CKL), Vietnamese Korean Learners(VKL), and Korean Native Speakers (KNS) in awareness of linguistic impoliteness. For this aim, the study sets two research questions : 1. Do CKL and VKL understand the literal utterance the same way as KNL do?, and 2. Do CKL and VKL understand the nonliteral utterance the same way as KNL do? Literal utterance include utterances with politeness and impoliteness, whereas nonliteral utterance refers to utterances with mock politeness and mock impoliteness. The study surveyed a total of 195 participants (65 from each group of KNS, CKL, and VKL) about their awareness on expressions of impoliteness, and applied a multiple response analysis on the results. As for the research question 1, CKL and VKL had a similar understanding as the KNS on the speakers’ attitude and intention. However, the cases of discrepancies between the learners and KNS were more frequent in utterances of impoliteness than politeness. As for the research question 2 on nonliteral utterance with mock politeness and mock impoliteness, although some learners understood nonliteral utterance the same way as KNL did, many took it for its literal meanings and understood the opposite of KNS. The discrepancies were especially wide in cases of superficially indirect and polite utterances using interrogative forms. The results imply the need to teach linguistic impoliteness and meanings that could vary depending on the situation context. Korean language learners’ misunderstanding and wrong reaction on linguistic impoliteness could cause a serious communication failure. This study could be a stepping stone for more research on linguistic impoliteness, and eventually to putting more emphasis on teaching impolite expressions on fields of education as opposed to conventional focus on positive nature of the language.
Keywords: 불손; 공손; 언어적불손 표현; 불손 이론; 축자적; 인식; 중국인 한국어 학습자; 베트남인 한국어 학습자; impoliteness; politeness; linguistic impoliteness; impoliteness theory; literal; awareness; Chinese Korean Learner; Vietnamese Korean Learner